Deteksi Dini Faktor Risiko Penyakit Tidak Menular pada Masyarakat Wilayah Maccini - Magdalena Limbong; Nurhayati Nurhayati; Jailani Tilitu; Ayu Nurkamiden (BADAN PENERBIT STIEPARI PRESS, 2021)
Non-Communicable Diseases (NCDs) are diseases that are not contagious and are not transmitted to other people through any form of contact, causing death and killing around 35 million people every year, or 60% of all deaths globally, with 80% prevalence in developing countries. NCDs, especially cardiovascular disease, cancer, chronic respiratory disease, and diabetes are major threats to human health and development today. The aim of this community service is to detect risk factors for non-communicable diseases in the people of the Maccini Region, Makassar City. The types of activities carried out include health education, checking blood pressure, cholesterol levels, instant blood sugar and uric acid. Screening and early detection of risk factors for non-communicable diseases was carried out on 67 respondents, including 14 men and 53 women. In the results of blood pressure checks, it was found that the number of people experiencing hypertension was 28.35%, normotension was 67.16%, and hypotension was 4.47%. On the Total Cholesterol examination, cholesterol was found to be within normal limits of 2.38% and high 37.31%. The results of the Temporary Blood Sugar (GDS) examination showed that the GDS level was within normal limits of 85.07% and the GDS level was high at 14.92%. On examination, uric acid was found to be within normal limits, namely 91.04% and high 8.95%. It is necessary to maximize posbindu activities in reducing the incidence of non-communicable diseases through education and screening.